Tunisian mothers’ perception of their young children’s interactive screen time at home - Fourati, Amel Meziane- (Southeast Asia Early Childhood Journal, 2017)
Nowadays, handheld digital tools such as tablets and smartphones are an integral part of a substantial number of households and their compelling nature lure youngsters. Indeed, their user-friendly design together with the wide range of accessible games, educational applications, and videos make them very popular among children as young as two (Lunch and Redpath, 2014). Therefore, it is an undeniable fact that digital use in the home environment can shape pre-school learning experiences and develop emergent numeracy and literacy skills including numbers knowledge, alphabet knowledge, print and phonological awareness (Kucirkova et al., 2013). However, several researchers, health experts, early childhood practitioners and parents have voiced their doubts and concerns about the suitability of using these tools as instructional aids during the early learning phase. Their scepticism is legitimate if one considers possible risks such as increased distractibility, social isolation and exposure to inappropriate content (House, 2012; Miller, 2005; Radesky et al., 2015). In contrast, others have highly approved of these new devices and claim that they can offer multiple opportunities for independent learning, collaboration, creativity and experimentation (Bandura, 2001). Whether digital handheld tools are beneficial or detrimental to children’s learning and development remains an on-going debate. Based on the responses of 52 Tunisian working mothers to a self-designed questionnaire and a semi-structured interview, this study aims at investigating various aspects related to Tunisian young children’s (aged 18 months to 5 years-old) use of smartphones and tablets at home including: frequency of exposure, reasons for use, mothers’ attitudes towards their children’s interactive screen time at home, the opportunities they feel these tools offer and the risks they associate with such powerful digital media